From a Medieval Town to the Modern Fortress of Rosas (Girona-Spain). Combining Geophysics and Archaeological Excavation to Understand the Evolution of a Strategic Coastal Settlement - Sabater Marc Bouzas; Grimal Lluís Palahí; Bartrolí Roger Sala; Órtiz-Quintana Helena; Simón Pedro Rodríguez (Open Archaeology)
The paper presents the results of the archaeogeophysical study carried out in the medieval villa of Rosas (Girona-Spain). The village was built in a space that had already been occupied in Greek and Roman times. In the sixteenth century, a large fortress was built around the town. Once the village was abandoned in the seventeenth century, the site underwent a major conversion process, with the construction of military buildings and the demolition of most of the medieval constructions. When it came to studying the village, its large size (20,000 m2) made it advisable to combine different methodologies and approaches in order to obtain optimum results. Some of the areas analysed by the geophysical surveys were subsequently tested archaeologically in order to verify their reliability, taking into account the specific conditions of the terrain. The combined use of geophysical prospecting, archaeology, and the study of historical planimetry and documentation has made it possible to reconstruct the town planning of the medieval villa, as well as the transformations it underwent after its abandonment.